Fe-modified sporopollenin as a composite biosorbent for the removal of Pb2+ from aqueous solutions. Issue 58 (13th December 2016) - Şener, Murat; Kayan, Berkant; Akay, Sema; Gözmen, Belgin; Kalderis, Dimitrios
Abstract: The role of Fe-modified sporopollenin (Fe-Sp) biomass in Pb 2+ removal from aqueous solutions was investigated by batch biosorption technique. The prepared biosorbent was characterized by scanning electron microscopy, energy-dispersive X-ray spectrometry, and Fourier transform infrared spectroscopy. The influence of pH, contact time, biosorbent dose, and initial concentration on biosorption process were optimized by using a four factor Box–Behnken design combined with response surface methodology. The results indicated a positive adsorption behavior of Fe-Sp and a strong pH dependency of the process. The optimum predicted parameters were determined as follows: biosorbent dosage 0.5 g, pH of 6.75, contact time 104 min, and initial Pb 2+ concentration of 25.42 ppm. The Freundlich isotherm model provided a better fit ( R 2  = 0.994) for the experimental data, indicating biosorption on a heterogeneous surface. Maximum biosorption capacity ( q max ) was 22.72 mg g −1 as indicated by the Langmuir isotherm. Kinetically, the adsorption process followed a pseudo-second-order model, indicating that chemisorption was the rate-limiting step.